TINDAKAN PENYELAMATAN KREDIT BERMASALAH DI BANK RAKYAT INDONESIA UNIT SIMPANG BARU PEKANBARU - Ikhsan '; Rika Lestari; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Reciprocal relationship between the Bank in this case Bank Rakyat Indonesia Unit Baru Simpang Pekanbaru and customers in lending does not always run smoothly, even not uncommon problem loans. The non-performing loans would interfere with the performance of the bank, so for that we need the efforts to overcome it. The purpose of this study, to determine the rescue action problem loans in Bank Rakyat Indonesia Baru Simpang unit Pekanbaru, to determine obstacles in the rescue action problem loans in Bank Rakyat Unit Indonesia Baru Simpang Pekanbaru, to know the efforts in overcoming obstacles problem loans in Bank Rakyat Unit Indonesia Baru Simpang Pekanbaru. This type of research is a sociological law research, because in this study the authors directly conduct research on locations or places studied in order to give a complete and clear picture of the problems examined. This research was conducted at the Bank Rakyat Indonesia Unit Baru Simpang Pekanbaru, while the sample population is a whole party with regard to the problems examined in this penelitiaan, data source used, primary data, secondary data and data tertiary, data collection techniques in this study with interviews and literature study. Actions rescue of troubled loans at Bank Rakyat Indonesia Unit Baru Simpang Pekanbaru done by means of rescheduling, reconditioning or restructuring but not for all customers. Obstacles in the rescue action problem loans in the form of barriers that arise when the restructuring will be carried out. Rescue efforts in problem loans is by delaying the reset credit agreement if one of the husband / wife was not present when the re-signing of loan agreement.To Bank Rakyat Indonesia Unit Baru Simpang Pekanbaru in order to take action to implement the rescue of troubled debt rescheduling process, reconditioning or restructuring for all customers in accordance with applicable regulations. To customers in order to complete the requirements when the restructuring process will be conducted. To Bank Rakyat Indonesia Unit Baru Simpang Pekanbaru in order to perform credit agreement, to make the agreement known by the notary. In order to have legal force.Keywords: Rescue- non performing loans